Effect of Local Floor Heating System on Occupants’ Thermal Comfort and Energy Consumption Using Computational Fluid Dynamics (CFD) - Hassan J. Dakkama; Ahmed Jawad Khaleel; Ahmed Qasim Ahmed; Wisam A. M. Al-Shohani; Hayder M. B. Obaida (Fluids, 2023)
In this article, the influence of splitting a local underfloor air distribution system (UFAD) on indoor thermal comfort for three occupants was studied numerically. A validated computational fluid dynamics (CFD) model was employed in this investigation. The proposed heating system was evaluated and analyzed for different values of air temperature and supply velocity. Providing suitable thermal comfort and saving energy are considered the main evaluation indexes for this study. Three cases, cases 2, 3, and 4, of the proposed local UFAD system were compared with a traditional heating system case, case 1. The supplying air velocity and air temperature in the reference case were 0.5 m/s and 29 °C, while in cases 2, 3, and 4, they were 0.4 m/s and 29 °C, 28 °C, and 27 °C, respectively. The results show that acceptable indoor human thermal comfort and energy demand reduction were achieved by using the splitting UFAD concept.